2020
DOI: 10.3389/fneur.2020.00581
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Thrombolysis on Acute Branch Atheromatous Disease: A Retrospective Case–Control Study

Abstract: Background and Objective: Branch atheromatous disease (BAD) is distinctive from large-artery atherosclerosis and small-vessel disease, which is single subcortical infarction caused by the occlusion of perforator's orifice. This study aimed to indicate whether intravenous thrombolysis (IVT) with alteplase could prevent early neurological deterioration (END) and improve functional outcome for patients with BAD within 4.5 h after symptom onset. Methods: We retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
(69 reference statements)
0
12
0
1
Order By: Relevance
“…[ 13 ] Cerebral infarction due to BAD is more common in Asia, especially in China. [ 14 ] In recent years, some scholars have demonstrated that the fluctuation or progression of neurological function is closely related to BAD, [ 15 , 16 ] wherein the fluctuation of neurological function mainly involves the progression of motor deficits, which usually leads to severe disability. Unfortunately, only a few studies are focused on the treatment of BAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] Cerebral infarction due to BAD is more common in Asia, especially in China. [ 14 ] In recent years, some scholars have demonstrated that the fluctuation or progression of neurological function is closely related to BAD, [ 15 , 16 ] wherein the fluctuation of neurological function mainly involves the progression of motor deficits, which usually leads to severe disability. Unfortunately, only a few studies are focused on the treatment of BAD.…”
Section: Discussionmentioning
confidence: 99%
“…The NINDS trial showed that alteplase was the most effective drug for improving clinical outcomes of ischemic stroke. [ 17 ] Wu et al [ 16 ] demonstrated that rt-PA infusion within 4.5 hours after the onset of symptoms significantly improved the early improvement rate of clinical symptoms in hyperacute BAD patients. The current study (n = 580) showed that intravenous alteplase administered within 4.5 hours of stroke onset increased EDR (35.2%) and more patients had favorable outcomes, which is consistent with a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…However, early neurological deterioration (END), observed in the acute phase of the infarction and leading to unexpected severe disability status, is not rare in these patients [6][7][8]9]. At present, intravenous thrombolytic therapy (IVT) is still the rst choice of treatment for SSI within the thrombolysis time window, although there are some controversies regarding the use of thrombolysis in the small pawn (NIHSS score ≤ 3) [10][11][12] . However, studies have shown that despite receiving IVT, a subset of those patients will still have END, which can affect the patient's long-term functional outcome [7][8]13 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The rate of END following intravenous thrombolysis was estimated as 13.8%, measured by the deterioration of NIHSS score at 24 h (≥ 4) [12]. Intravenous thrombolysis seemed unable to prevent END and controversial about its effect on improving functional outcome among patients with BAD-related stroke [12,[17][18][19]. In addition, Seners P, et al found that strongest predictors for END were consistent across thrombolysed and non-thrombolysed acute ischemic stroke patients including hyperglycemia, proximal arterial occlusion, large infarcts, no recanalization or re-occlusion, and etc.…”
Section: Introductionmentioning
confidence: 99%